Aktivitas Antibakteri TiO2-Anatas Terdadah -Vanadium dan -Kromium - Hari Sutrisno; Ariswan Ariswan; Dyah Purwaningsih (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Samples of vanadium- and -chromium doped TiO2-anatas have been conducted antibacterial activity against the bacteria Escherichia coli (E. Coli). The minimum kill concentration (MBC) against the bacteria of E. Coli is determined by liquid dilution method. The antibacterial activity test of 0; 2.3; 3.3; 4.9% wt. vanadium doped TiO2-anatas and 0; 1.1; 3.9; 4.4% wt. chromium doped TiO2-anatas have been performed against bacteria of E. Coli in the absence of light (dark). The test results indicate that the presence of 3.3 and 4.9 in %wt. vanadium-TiO2-anatas are able to inhibit the growth of bacteria E. Coli, contrary all chromium doped TiO2-anatas are not able to inhibit the growth of bacteria of E. Coli.